Election Supervision Training for Sub-District/Village Supervisors in Pemenang District, North Lombok Regency - Uli, Aprilla Sinta; Junaedi, Junaedi; Rosdiyanti, Evi; Azim, Muhammad; Anwar, Sairil; Irmayani, Resbi (Abdi Masyarakat, 2024)
Election Supervision Training for Subdistrict/Village Supervisors in Pemenang District, North Lombok Regency, aims to increase the capacity of election supervisors at the local level in carrying out supervisory duties effectively, efficiently and in accordance with applicable regulations. This training was carried out using a participatory-based approach that integrated lecture methods, group discussions, case studies, supervision simulations, and the use of technology in election supervision. A total of 40 sub-district/village supervisors took part in training which lasted for three days, with material covering election regulations, supervision techniques, handling violations, and the use of digital-based monitoring applications. The evaluation results showed a significant increase in participants' understanding of election regulations and technical skills in supervision, with an average increase in test scores of 25%. Additionally, 90% of participants reported increased understanding regarding the use of technology in election reporting and monitoring. However, this training also faced several challenges, especially related to limited technological infrastructure in remote areas and differences in participants' levels of understanding. Overall, this training proved effective in strengthening the capacity of election observers at the sub-district/village level, but required strengthening infrastructure and adapting materials to overcome existing challenges.